Inductive linearization for binary quadratic programs with linear constraints: a computational study - Sven Mallach (4OR, 2023)
The computational utility of inductive linearizations for binary quadratic programs when combined with a mixed-integer programming solver is investigated for several combinatorial optimization problems and established benchmark instances.
Keywords: 650; Non-linear programming; Binary quadratic programming; Mixed-integer programming; Linearization